THE DEVELOPMENT OF MODERN THEOLOGY - Abdul Wahab Syakhrani; Ahmad Zaini (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
This modern age is also the spirit of the new age that existed in the 19th century. As a form of civilization and the spirit of the times, modernity is characterized by 3 things, namely individualism, rationalism and progress. Therefore, modern technology  is  able  to  compete  in  the  current  era  of technological development.